Effects of sugar molecules on the rheological and tribological properties and on the microstructure of agarose-based fluid gels - Ghebremedhin, Marta; Seiffert, Sebastian; Vilgis, Thomas A. (Frontiers in Soft Matter, 2024)
Fluid gels exhibit viscoelastic behaviour, which involves the coexistence of solid and fluid properties on different time scales. These irregular particle structures with their heterogeneous shape demonstrate plasticity and yielding, transitioning from a solid to a fluid-like state. This is also defined by the core of the particles, but also by the structure of the surfaces of the particles. Notable, the addition of cosolutes, such as sucrose, change the network properties at microscopic scale, thereby significantly impacts their textural and lubricating properties. Hence, these microscopic changes are reflected in macroscopic changes. Increasing sucrose concentration leads to the formation of microgel particles with different sizes, diverse shapes, and interconnected network structures, as revealed by particle structure and size characterization. These alterations in microstructure are closely related to the dynamic competition between gelation and disruption during shear of the agarose chains, directly influencing the rheological and tribological properties of fluid gels. However, it also influences the association of the agarose chains, their gelation process and thus the behaviour of the fluid gel, depending on whether the sucrose was first dissolved in water or in agarose. The experimental observations suggest specific molecular mechanisms explaining the molecular interplay and the role of sucrose in structure formation in agarose-based fluid gels. These findings have the potential to expand the applications of fluid gels, which play a crucial role in modifying the texture and flow behaviour of foods and beverages, particularly in addressing challenges such as dysphagia.Different chain associations for agarose by forming helical structures at the molecular level have been suggested to influence mechanical properties, as reported by Matinez-Sanza et al. (2020). These authors proposed that agarose chains in some of the samples do not only exist in a coil structure at a temperature of 75°C, but also in some form of molecular association, indicating a variety of hierarchical structures (Martínez-Sanz et al. 2020). Thus, some agarose did not show true solution behaviour (at 75°C) but rather the behaviour typical of a transient (entangled) network. They reported that although